Identification of Differentially Expressed Genes and Elucidation of Pathophysiological Relevance of ABCA1 in HaCaT Cells Induced by PM2.5 - Fen Peng; Chen-Hong Xue; Xiao-Jing Yang; Jing-Yi Huang; Zhou Chen; Jian-Zhong Zhang (Bioinorganic Chemistry and Applications)
Objective. In order to investigate the effects of PM2.5 on proliferation, cell cycle, apoptosis, and potential mechanism of human keratinocyte cell line HaCaT. Methods. HaCaT cells were treated with different concentrations of PM2.5 suspension for 24 hours. Cell viability was detected by the CCK-8 method. Cell cycle distribution and apoptosis were detected by flow cytometry. Microarray analyses were used to find out the microarray gene expression profiling; data processing included gene enrichment and pathway analysis. Western blot was conducted to validate the key pathways and regulators in the microarray analysis. Results. The cell activity decreased, and the cell cycle was significantly inhibited with the increase in PM2.5 concentration. Also, by conducting the gene expression microarray assay, we identified 541 upregulated genes and 935 downregulated genes in PM2.5-treated HaCaT cells. Real-time qPCR and western blot confirmed that PM2.5 treatment could induce the expression of ABCA1 while inhibiting that of END1 and CLDN1. Conclusion. Our results showed that PM2.5 could potentially regulate cell apoptosis and cell cycle arrest via ABCA1-, END1-, ID1-, and CLDN1-mediated pathways in human HaCaT cells, which laid a good foundation for follow-up drug intervention and drug development against skin damage caused by PM2.5 exposure.